Design of Expert System for Hard Skill Competencies- Based Employee’s Performance Evaluation - Faqih Maulana; Usman Effendi; Arif Hidayat (APTA and DTIP FTP UGM, 2017)
The quality of human resources is one of the important factors to maintain the sustainability of a company, therefore it is essential for the company to evaluate performance of its employees. With the recent rapid development of computer technology, especially in the field of artificial intelligence, many problems can now be effectively addressed with the help of computer. The purpose of this research is to design an expert system for hard skill competencies-based employee performance evaluation. The system is expected to be able to give accurate recommendations on decision making process of several human resources’ issues such as recruitment, training, transfer, and promotion in the filling plant division. This research uses descriptive analysis, prototyping, gap analysis and Analytical Network Process (ANP) to build a system which will function like an expert in evaluating the performance of employees. This system contains knowledge domain in 7 position levels of SMART’s filling plant employees. Critical factors of this system are mastery of basic work health and safety, ability on operating filling plant machines, ability on machine maintenance and mastery in quality management system. Results of the system test show that the proposed expert system had been running well in accordance with the rules in the decision table and had been considered to be able to meet human expert representation.